Development of e-wallets and cashless payments: Evidence from Vietnam and implications for emerging economies - TRAN, Thi Lan; HOANG, Phuong Hoa (Edelweiss Applied Science and Technology, 2026)
Recently, the expanding digital economy has led to a strong rise in the number of cashless payments in Vietnam, in which e-wallets are becoming an icon of financial innovation. This research aims to discover factors driving the adoption of e-wallets in Vietnam, assessing the impact of e-wallets on financial inclusion, as well as implementing recommendations for emerging economies during economic transformation. The research integrates the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) within a Structural Equation Modeling (SEM) framework, using a mixed dataset that combines survey data from 1,268 e-wallet users with secondary data from the State Bank of Vietnam, the World Bank, GSMA, and industry reports. The findings indicate that performance expectancy and trust are the most significant drivers of e-wallet usage, and e-wallet usage has the strongest positive and statistically significant impact on financial inclusion. The study concludes that e-wallets are an effective gateway to financial services in emerging markets, particularly in the context of rapid digital infrastructure development. Practical implications suggest that policymakers should strengthen legal frameworks and data protection, narrow the gap in access to financial services, and promote financial literacy to maximize the inclusive benefits of digital payments.